A lanthanide MOF immobilized in PMMA transparent films as a selective fluorescence sensor for nitroaromatic explosive vapours. Issue 11 (6th March 2020) - Moscoso, Francisco G.; Almeida, José; Sousaraei, Ahmad; Lopes-Costa, Tânia; Silva, Ana M. G.; Cabanillas-Gonzalez, Juan; Cunha-Silva, Luís; Pedrosa, José M.
Abstract : A selective luminescent sensor was fabricated by simply mixing a Tb(iii )-based MOF with polymethylmetahacrylate enabling to detect sub-ppb range of nitroaromatic vapours. Abstract : This study introduces a highly selective and sensitive luminescent sensor based on simply mixing a Tb(iii )-based luminescent Metal–Organic Framework with polymethyl-methacrylate enabling to detect sub-ppb range of nitroaromatic vapours, properly. To the best of our knowledge, this is the first report on the use of this material for detecting gaseous analytes. Meanwhile, the present sensor dispels previous doubts about the selectivity and sensitivity of this material for the detection of nitroaromatic explosives in liquid media along with its applicability in the presence of potential interferences.